Preservation and Promotion of the Rraditional Chèo in Vietnam today - Le, Tuan Cuong (H. : ĐHQGHN, 2020)
Chèo is a form of traditional folk art performance of Vietnam, originated about 10 centuries ago. Cheo derives from folk music and dance, especially parody. This form is the result of artistic creation of Vietnamese peasants in northern Vietnam to Nghe An and Ha Tinh. Since its introduction, Cheo has received the attention and love among people of all classes for centuries. Quan Am Thi Kinh, Luu Binh Duong Le, Truong Vien and Kim Nham together with famous chiếng chèo: chiếng chèo Doai, chiếng chèo Bac, chiếng chèo Dong, etc. showed intense vitality and the spread of Chèo. However, along with the history of national struggle, innovation, socio-economic development, especially international integration, many new types of culture have been introduced to Vietnam while traditional art has not caught up and met the requirements of the public. It has directly contributed to weakening the values of traditional culture in general and folk art including Chèo in particular. By analyzing historical and cultural documents, the article focuses on the process of formation and development of Vietnamese Chèo in history, from which to look at the contemporary of this art form and propose measures for preservation and promotion.